FREQUENCY OF REFRACTIVE ERROR AND AMBLYOPIA IN STRABISMUS IN PEDIATRIC AGE GROUP - Noureen Malik (Army Medical College Rawalpindi, 2021)
Objective: To see the frequency and compare the type of refractive error and strabismus in amblyopic versus non amblyopic children.